A Universal Strategy for Constructing Robust and Antifouling Cellulose Nanocrystal Coating. (9th November 2021) - Yang, Wenshuai; Pan, Mingfei; Zhang, Jiawen; Zhang, Ling; Lin, Fengcai; Liu, Xiong; Huang, Charley; Chen, Xing‐Zhen; Wang, Jianmei; Yan, Bin; Zeng, Hongbo
Abstract: Super‐hydrophilic cellulose nanocrystals (CNCs) hold great potential in fabricating antifouling surfaces based on their high‐water binding affinity. However, integrating CNCs as a robust surface coating on substrate still remains a challenge due to its limited surface adhesion property. Herein, inspired by marine bio‐adhesive strategy, a facile yet universal surface coating method is developed for tightly anchoring CNCs on various substrates with an intermediate adhesive layer composed of tannic acid (TA)/polyethylenimine (PEI)/vanadium(V). Introducing V 3+ ions in the assembly process significantly reduces the roughness of the TA/PEI/V bio‐glue layer via coordination chemistry, thus achieving a CNCs coating with a highly‐dense structure and outstandingly low root‐mean‐square roughness (≈2 nm). The super‐hydrophilic CNCs coating exhibits universal and outstanding antifouling properties in inhibiting oil adhesion, protein adsorption or cell attachment, and maintaining its structural integrity and wettability over 100 friction cycles. Additionally, the CNCs‐coated polyvinylidene fluoride (PVDF) membrane shows an ultra‐high water flux over 6000 L m –2 h –1 bar –1 and achieves nearly 100% permeating flux recovery ratio for separation of toluene‐in‐water emulsion containing various foulants. This study demonstrates a universal coating method to settle the long‐standing challenge of robust integration of rigid materials to various substrates for broad engineering and environmental applications. Abstract : A universal and scalable cellulose nanocrystals (CNCs) coating strategy is proposed and developed via robustly grafting CNCs onto various substrates by constructing an intermedia adhesive layer. The highly dense CNCs coating exhibits outstanding antifouling and anti‐wear performance for water purification. This study provides a useful method for addressing a long‐standing challenge of the integration of rigid materials as robust surface coatings.